The future perspective for Mopti - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The fifth region of Mali around Mopti, has considerable potential for agriculture and fisheries. But, if the area's limitations in natural and human resources are not heeded, there will be no future for the development of crops, cattle or fish. A...